2021
DOI: 10.1186/s40068-021-00230-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modelling of perception for sustainable agriculture as climate change mitigation strategy in Ghana

Abstract: Background Ghana’s agriculture sector has contributed significantly to the country’s Gross Domestic Product (GDP) over the past decades even though there has been persistent decline of about 12.8% in the last 7 years. It decreased from 31.8% in 2009 to merely 19% as of September 2015, a period of 7 years. In spite of these trends, sustainable agriculture has been observed to be a game changer in agricultural development and growth globally. Sustainable agriculture is partly dependent on the att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Previous studies [3,4,[80][81][82] have demonstrated that SEM is a powerful and flexible method for analyzing the complex relationships among multiple and diverse variables affecting the agricultural sector. SEM allows researchers to model intricate interactions among observed and unobserved variables, making it well suited for testing and validating complex theoretical models, as emphasized by Garson [79] and Hair et al [78].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [3,4,[80][81][82] have demonstrated that SEM is a powerful and flexible method for analyzing the complex relationships among multiple and diverse variables affecting the agricultural sector. SEM allows researchers to model intricate interactions among observed and unobserved variables, making it well suited for testing and validating complex theoretical models, as emphasized by Garson [79] and Hair et al [78].…”
Section: Methodsmentioning
confidence: 99%
“…To satisfy the discriminant validity of the model, the correlation of any two items between the latent variables should be less than the square root of the AVE value that was shared by its items within that latent variable [16,19]. Both the MSV and ASV of the exogenous variables are less than the AVE, and this indicates that there are no discriminant concerns to develop the model [33][34][35][36][37][38]. Table 8 satisfies the discriminant validity (implying multicollinearity is absent), as the correlations of any two items between the latent variables is found to be less than the square root of AVE values within that latent variable.…”
Section: Sem Analysis-measurement Modelmentioning
confidence: 99%
“…The structural model presenting the estimated coefficients of the exogenous variables to the latent endogenous variable (Figure 3) forms the basis for hypothesis testing [7,30,35,38,46]. The computed standardized total effects (Table 11) showed that strengthening SS is the most effective indicator influencing CPD among the ID construct.…”
Section: Sem Analysis-structural Modelmentioning
confidence: 99%
“…Yu et al ( 2021) established an association between socioeconomic factors and soil erosion, and Chandra and Kumar (2021) examined the relationship between vaccine use and economic performance. Ankamah et al (2021) explained the perception of agricultural sustainability in regard to mitigating climate change in Ghana. The results of Ankamah et al (2021) show that social features and resource information influence the adoption of sustainable agricultural practices.…”
Section: Introductionmentioning
confidence: 99%
“…Ankamah et al (2021) explained the perception of agricultural sustainability in regard to mitigating climate change in Ghana. The results of Ankamah et al (2021) show that social features and resource information influence the adoption of sustainable agricultural practices. This study uses SEM to construct a model for duck farming sustainability in Indonesia.…”
Section: Introductionmentioning
confidence: 99%